Eyes for Machines: A Computer Vision Approach to Enhance Robotic Arm Dexterity and Autonomy - Balkrishna Rasiklal Yadav (International Journal of Advanced Control and System Engineering, 2024)
By combining sophisticated robotics and visual awareness, computer vision operated robotic arms have revolutionized technology. These devices are having a profound effect on several industries, from manufacturing processes to healthcare. Computer vision–controlled robotic arms are altering the game with their ability to see, comprehend, and interact with their surroundings. In this study we have tried to develop and implement software and hardware to improve the freedom of movement in a robotic arm which will have a similar look to hand gestures. In the modern world, robotic arms are becoming essential, with uses in a wide range of sectors, including military, defense, healthcare, and industrial automation. These amazing devices can replicate the movements and hand gestures of a human, which makes them incredibly useful in a variety of scenarios. The most innovative automation technology available now is robotic systems. Initially, robots were employed on manufacturing floors in the 1960s and early 1970s. Evaluating the precision of system was done by methods such as sorting, kinematic modeling, and center recognition which elevate the movements of robotic arms. More innovation to elevate the free movement of robotic arms can enhance its applications at defense and industrial level.
Keywords: Defense; Robotics; hand gestures; kinematic modeling; point to point trajectory